Neuralgic Amyotrophy with Concomitant Hereditary Neuropathy with Liability to Pressure Palsy as a Cause of Dropped Shoulder in a Child after Human Papillomavirus Vaccination: A Case Report - Hye-Chan Ahn; Do-Hoon Kim; Chul-Hyun Cho; Jun-Chul Byun; Jang-Hyuk Cho (MDPI AG, 2022)
Hereditary neuropathy with liability to pressure palsy (HNPP) makes nerves increasingly susceptible to mechanical pressure at entrapment sites. Neuralgic amyotrophy (NA) can cause sudden regional weakness following events to which the patient is immunologically predisposed, such as vaccination. However, NA related to human papilloma virus (HPV) vaccination is seldom reported. We describe the case of a child with NA as the cause of a dropped shoulder following the administration of the HPV vaccine. Underlying asymptomatic HNPP was confirmed in this patient based on the electrodiagnostic findings and genetic analysis. We speculate that HPV vaccination elicited an immune-mediated inflammatory response, resulting in NA. Our patient with pre-existing HNPP might be vulnerable to the occurrence of an immune-mediated NA, which caused the dropped shoulder.